Implementing routine paediatric height/length and weight screening and weight management advice by clinicians: an evaluation - Slavica Krstic; Sarah Dennis; Faye Southcombe; Elizabeth Denney-Wilson (BMC, 2024)
Abstract Objective To determine the views of health care professionals (HCPs) in South Western Sydney Local Health District (SWSLHD) about the effectiveness of implementation strategies used to increase routine height/length and weight screening, advice, and referral for children and adolescents. A secondary aim was to explore the prevalence of weight bias among HCPs. Methods A questionnaire was sent to all HCPs who had undertaken online or face-to-face training between December 2018 and June 2020 in SWSLHD (n=840). The questionnaire collected data on their experience of routine height and weight screening and the effectiveness of strategies used in the implementation. It also included a weight bias assessment. Data were provided by the New South Wales (NSW) Ministry of Health on the performance of routine height/length and weight measures entered into the electronic medical records (eMR) in SWSLHD. Results Of the 840 questionnaires sent, 87 were undeliverable; of the remaining 753, 285 were returned (38% response rate). More than half (53%, 151/285) of the participants were nurses. Most HCPs agreed that there was a need for routine screening and reported that education, training, and access to resources were the most helpful implementation strategies. Most HCPs were confident in performing routine screening but were less confident in raising the issue of weight with children and their families. Barriers to implementation were lack of time, equipment, appropriate clinical setting, and HCPs' perceptions and beliefs about obesity. Conclusion Routine screening is the first step in identifying children and adolescents at risk of overweight and obesity, but many HCP found it challenging to incorporate into daily practice. Multifaceted strategies are effective in increasing routine screening across diverse healthcare settings so that children and adolescents receive timely and appropriate intervention.